Estimating policy effects on spatial market efficiency: An extension of the parity bounds model - Negassa, A.; Myers, R.J. (Wiley, 2007)
The standard parity bounds model (PBM) is extended to allow for dynamic shifts in regime probabilities in response to changes in marketing policy. The approach allows estimation of the length of the adjustment period and a statistical test for no policy effects. The extended PBM is applied to maize and wheat markets in Ethiopia. Evidence of a dynamic adjustment path is found and grain marketing reforms are found to have improved spatial efficiency in a few markets, worsened it in a few others, but generally to have had little effect on the spatial efficiency of Ethiopian grain markets.